THE INFLUENCE OF SWITCHING BARRIERS AND INERTIA ON CUSTOMER LOYALTY OF MAYBELLINE BEAUTY PRODUCT - Somnaikubun, Monica Yunita; Tumbuan, Willem J. F. A.; Arie, Fitty Valdi (Universitas Sam Ratulangi, 2020)
Abstract: Nowadays, there is too much competition in the world of beauty, like many cosmetic brands selling their products to get the attention of women in this world. Switching Barriers and Inertia becomes a surefire marketing strategy to get and keep the hearts of consumers to continue to choose the product. The purpose of this study was to analyze the effect of Switching Barriers and Inertia on Customer Loyalty on Maybelline beauty products. This study uses a quantitative method with a questionnaire to collect data, and Multiple Linear Regression as an analysis tool. The sample in this study was 96 customers of Maybelline beauty products. The findings reveal that Switching Barriers has a positive relationship and a significant influence on Customer Loyalty, and Inertia has a positive relationship and a significant effect on Customer Loyalty. From the results, it is recommended for marketers to consider expanding the benefits of their products by improving the quality of their products through Switching Barriers and Inertia to make customers loyal to their products even though there are many competitors offering other products.Â Keywords: switching barriers, inertia, customer loyalty